1981
DOI: 10.1111/j.1365-2133.1981.tb15306.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent urticaria: clinical investigation of 330 patients

Abstract: A questionnaire was used from 1972-1978 for 330 consecutive patients with recurrent urticaria of 3 months to 40 years duration. Fifty men and fifty women had only urticaria. The rest had both urticaria and angio-oedema and most of them were women between 24 and 38 years of age. Urticarial attacks were less frequent during the daytime. A personal history of rhinitis, asthma or atopic dermatitis was recorded in more than one-third. Nasal polyps, migraine and arthralgia were found in 6-7% of the patients. Severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
7
13

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(197 citation statements)
references
References 16 publications
13
159
7
13
Order By: Relevance
“…An alternative pathogenic mechanism hypothesized (Lessof, 1991) is a reduction of the intestinal barrier against chemical compounds, such as histamine, contained in some foods that may trigger pseudoallergic reactions. In fact, many patients suffering from CIU attribute their symptoms to food intolerance (Julin, 1981;Sayag et al, 1988;Bischoff & Manns, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative pathogenic mechanism hypothesized (Lessof, 1991) is a reduction of the intestinal barrier against chemical compounds, such as histamine, contained in some foods that may trigger pseudoallergic reactions. In fact, many patients suffering from CIU attribute their symptoms to food intolerance (Julin, 1981;Sayag et al, 1988;Bischoff & Manns, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic idiopathic urticaria (CIU) is de®ned as repeated episodes or even continuous urticaria of unknown origin (Champion, 1988;Kaplan, 1988) and without any evidence if IgE mediated reaction (Warin, 1976). About 30 ± 40% of patients with chronic urticaria attribute their symptoms to food intolerance (Julin, 1981;Sayag et al, 1988), even if the affected person is seldom able to exactly identify the causative food. The possible pathogenic role of pseudoallergic reactions to food has been repeatedly discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In our patients, urticaria was more common in males and the Saudi nationals outnumbered other nationalities. Previous studies showed either no sexual or racial predilection 7,14 or females predominated over males. 15 Urticaria was found to affect all age groups and the highest incidence was among young adults as in other studies.…”
Section: Prevalence and Incidencementioning
confidence: 99%
“…The physical urticarias can be identified from the history and their diagnosis can easily be confirmed by specific and simple clinical tests. 8,25 Urticaria had been reported with a wide variety of pathologic and systemic disorders; 14,15,20,21 however, its association with internal diseases was thought to be uncommon. 26 In this study, a miscellaneous group of underlying systemic causes was identified and included the urticarias associated with pregnancy, systemic lupus erythematosus, diabetes, thyrotoxicosis, malignancy and hereditary angioedema.…”
Section: Etiological Factorsmentioning
confidence: 99%
“…Patients with urticaria may have symptoms of pruritus, wheals (edematous, erythematous central clearing papules or plaques) and swelling of mucous membrane when it co-exists with angioneurotic edema (Kaplan, 2002). Other psychological symptoms may include depression and anxiety and; severity of pruritus appears to increase as depression worsens (Juhlin, 1981;Finlay, 2000). Generally, patients with skin disorders tend to avoid social company in order to prevent public ridicule and rejection.…”
Section: Introductionmentioning
confidence: 99%